A systematic review and meta‐analysis of 18F‐labeled amyloid imaging in Alzheimer's disease. Issue 1 (1st March 2015) - Yeo, Jing Ming; Waddell, Briony; Khan, Zubair; Pal, Suvankar
Abstract: Background: Amyloid imaging using fluorine 18–labeled tracers florbetapir, florbetaben, and flutemetamol has recently been reported in Alzheimer's disease (AD). Methods: We systematically searched MEDLINE and EMBASE for relevant studies published from January 1980 to March 2014. Studies comparing imaging findings in AD and normal controls (NCs) were pooled in a meta‐analysis, calculating pooled weighted sensitivity, specificity, and diagnostic odds ratio (OR) using the DerSimonian‐Laird random‐effects model. Results: Nineteen studies, investigating 682 patients with AD, met inclusion criteria. Meta‐analysis demonstrated a sensitivity of 89.6%, a specificity of 87.2%, and an OR of 91.7 for florbetapir in differentiating AD patients from NCs, and a sensitivity of 89.3%, a specificity of 87.6%, and a diagnostic OR of 69.9 for florbetaben. There were insufficient data to complete analyses for flutemetamol. Conclusions: Results suggest favorable sensitivity and specificity of amyloid imaging with fluorine 18–labeled tracers in AD. Prospective studies are required to determine optimal imaging analysis methods and resolve outstanding clinical uncertainties.